Kepercayaan Diri Dan Kemampuan Berkomunikasi Dalam Pembelajaran Matematika: Systematic Literature Review - Siregar, Yulia Pratiwi; Siregar, Enni Sari (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to see the extent to which students' self-confidence in improving mathematical communication skills. The study also examines several other aspects that can improve students' mathematical communication skills. The research method used in this study is the Systematic Literature Review (LSR) using 3 steps, namely the stage of collecting articles on Google Scholar and Sinta. At this stage, 35 research articles were obtained, then the second stage was carried out, namely identification. In this second stage, elimination was carried out on the articles obtained because the articles did not match the focus of the research according to the stated research objectives. The next stage is the stage of critical analysis of the five articles that have been obtained. Based on this analysis, it was concluded that good mathematical communication skills occur if the characteristics of the student's self-confidence are in the high and medium categories, while students with low self-confidence characteristics have an impact on poor mathematical communication. In addition, good mathematical communication can also occur by paying attention to gender equality and providing new learning experiences so that students can explore all the abilities that exist in each of them. This learning experience can be done by using a project-based learning model and is related to everyday life